Comprehensive Study of Landslides through the Integration of Multi Remote Sensing Techniques： Framework and Latest Advances - 钟成 李卉 项伟 苏爱军 黄先锋 (Journal of earth science (Wuhan, China), 2012)
Detecting the timing and amount of deformation is critical for understanding the physical causes and eventually warning of possible landslide hazards. Monitoring of deformation of structures and ground surface displacements during landslides can be accomplished by using different types of systems and techniques. Besides geotechnical or physical techniques, remote sensing techniques can be classified as satellite techniques, photo-grammetric techniques, geodetic techniques, ground based techniques, and so on. To study and govern growing geological disasters in China, especially in the Three Gorges area, Three Gorges Research Center for Geo-hazard （TGRG） is establishing an infra structure to ef-fectively and comprehensively analyze the mechanism of landslide deformation, focused on the Huangtupo landslide, using of various ad-vanced monitoring systems and techniques. In this article, the framework and latest advances of integration of multi remote sensing techniques in the infrastructure are presented. Different remote sensing techniques, data processing and integrating methods, and the latest results are discussed in detail. At last, reviews on current work and suggestions for further work are put forward.